Hot-rolled steel material for cans and method for producing same

By adjusting the chemical composition and hot rolling process of austenitic stainless steel, especially controlling the hydrogen content and cooling speed, the delayed fracture problem of austenitic stainless steel hot rolled steel after plastic processing is solved, and high tensile strength and Hot-rolled steel for corrosion-resistant tanks.

CN119325521APending Publication Date: 2025-01-17NIPPON STEEL STAINLESS STEEL CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380045369.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-04
Filing Date
2023-06-30
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

Austener-based stainless steel hot-rolled steel is prone to delayed fracture after plastic processing, and the tensile strength is insufficient, making it difficult to meet the end plate material requirements of the tank.

Method used

By adjusting the chemical composition, ensure that the Md30 value is below 35°C, the hydrogen content in the surface layer is below 3.5 mass ppm, and hot rolling is carried out in a specific atmosphere of water vapor partial pressure and oxygen partial pressure to avoid solid solution heat treatment, control cooling speed, and prepare Hot rolled austenitic stainless steel with tensile strength of more than 600MPa.

Benefits of technology

It effectively prevents the occurrence of delayed fracture, improves the tensile strength and corrosion resistance of steel, and is suitable for end plate materials of low-temperature tanks.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005173664630000151
    Figure BDA0005173664630000151
  • Figure BDA0005173664630000161
    Figure BDA0005173664630000161
  • Figure BDA0005173664630000171
    Figure BDA0005173664630000171
Patent Text Reader

Abstract

A hot-rolled steel material for cans having, in mass%, 18.0-20.0% of Cr and 8.0-13.0% of Ni, an Md30 represented by formula (1) of 35 DEG C or less, an H (hydrogen) content of 3.5 mass ppm or less in a surface layer portion extending from the surface of the steel material to 1 / 5 of the plate thickness in the depth direction, and a tensile strength of 600 MPa or more. Md30 (DEG C) = 413-462 (C + N)-9.2, Si-8.1, Mn-13.7, Cr-9.5 (Ni + Cu)-18.5 and Mo (1).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a hot-rolled steel material for tanks and a method for producing the same, and more particularly to an austenitic stainless steel hot-rolled steel material for tanks for carrying low-temperature fuels and a method for producing the same. Background Art

[0002] Austenitic stainless steel is suitable as a material with excellent corrosion resistance and excellent toughness at low temperatures. Utilizing this characteristic, austenitic stainless steel is excellent as a steel material for low-temperature tanks. In austenitic stainless steel, since corrosion resistance deteriorates due to precipitates in the hot-rolled state, in the usual manufacturing method, solution heat treatment is performed after hot rolling to reduce precipitates. As a result of solution heat treatment, the tensile strength is only about 400 MPa at most.

[0003] In order to improve the strength of austenitic stainless steel, a method of omitting solution heat treatment and performing hot rolling under specific temperature conditions has been proposed. For example, Patent Document 1 discloses a manufacturing method, which is a manufacturing method of austenitic stainless steel containing a specified component, wherein a specified homogenization heat treatment is applied to the steel billet before hot rolling, and a specified rapid cooling (controlled cooling) is performed after hot rolling, and no solution heat treatment is performed. Thus, a hot-rolled austenitic stainless steel material that ensures low-temperature toughness, good seawater resistance, and high strength is achieved. Segregation is diffused by homogenization heat treatment before hot rolling, and re-precipitation of intermetallic compounds is suppressed by controlled cooling after hot rolling, and recovery of processing strain introduced in finish rolling is suppressed. By omitting solution heat treatment, high strength can be maintained. Steel manufactured by such a manufacturing method (hot working control) is also referred to as TMCP material (Thermo-Mechanical Control Process).

[0004] Austenitic stainless steel hot-rolled steel is used as a raw material to manufacture tanks, especially low-temperature tanks. Here, in order to manufacture bag-type tanks, it is necessary to apply plastic working to the steel to manufacture a member called an end plate (also called a cover plate or a head). In the general use of austenitic stainless steel thick plates, strong plastic working is rarely applied, and the above-mentioned end plate of the tank is characterized in that strong plastic working can be applied.

[0005] For austenitic stainless steel sheets other than the thick-walled steel materials (especially thick plates) that are the subject of the present invention, the material is used as a raw material for deep drawing by taking advantage of its high processability. In addition, in order to obtain the gloss on the surface, bright annealing is performed at the stage of the steel strip. It is known that austenitic stainless steel subjected to deep drawing, especially in the case of bright annealing, will produce delayed fractures called spontaneous cracking (also called natural cracking or seasonal cracking) if the processing rate exceeds the limit. Hydrogen invades the steel during bright annealing. It is said that the transformation martensite phase after deep drawing, residual stress, hydrogen in the steel, processing conditions, etc. are the main factors that control spontaneous cracking (see non-patent document 1).

[0006] In non-patent document 2, Md30 is proposed as an evaluation index of austenite stability of austenitic stainless steel. Md30 is the temperature (°C) at which the microstructure changes to 50% martensite phase when a tensile true strain of 0.30 is applied to an austenite single-phase sample. The higher the temperature, the more unstable the material. In non-patent document 2, in addition to the Md30 formula (formula (1)) proposed by Angel as a function of the component composition of steel, the Md30 formula (formula (6)) advocated by the document is also proposed.

[0007] Prior art literature

[0008] Patent Literature

[0009] Patent Document 1: Japanese Patent Application Publication No. 2006-241590

[0010] Non-patent literature

[0011] Non-patent document 1: Stainless Steel Handbook, pages 927-929

[0012] Non-patent document 2: Nohara et al., “Composition and grain size dependence of work-induced martensitic transformation in metastable austenitic stainless steel,” Iron and Steel 63 (1977), No. 5, pp. 772-782 Summary of the invention

[0013] Problems to be solved by the invention

[0014] The following austenitic stainless steel hot-rolled steel material was used as a raw material for an end plate of a tank. As a result, it was found that delayed fracture occurred after plastic working as the end plate. The austenitic stainless steel hot-rolled steel material was a thick plate that had not been solution heat treated and had a tensile strength of 600 MPa or more.

[0015] The object of the present invention is to provide a hot-rolled steel material for a can that does not cause delayed fracture after plastic working when an austenitic stainless hot-rolled steel material, i.e., a thick plate that has not been solution heat treated, is used as a raw material for an end plate of a can and a method for producing the same.

[0016] Means for solving problems

[0017] That is, the gist of the present invention is as follows.

[0018] [1] A hot-rolled steel material for cans having the following chemical composition: in terms of mass%, C: 0.08% or less, Si: 0.05-1.0%, Mn: 0.10-2.0%, P: 0.045% or less, S: 0.030% or less, Cr: 18.0-20.0%, Ni: 8.0-13.0%, Mo: 1.0% or less, Cu: 1.0% or less, N: 0.05-0.10%, Al: 0.10% or less, the remainder being Fe and impurities,

[0019] The Md30 represented by the formula (1) is 35°C or less,

[0020] The H (hydrogen) content in the surface layer portion from the surface of the steel material to 1 / 5 of the plate thickness in the depth direction is 3.5 mass ppm or less,

[0021] The tensile strength has a value of 600 MPa or more.

[0022] Md30(℃)=413-462(C+N)-9.2Si-8.1Mn-13.7Cr-9.5(Ni+Cu)-18.5Mo(1)

[0023] In the formula (1), the element symbol on the right side refers to the content (mass %) of the element in the steel. In addition, the above-mentioned "hot-rolled steel material" refers to a steel material in a hot-rolled state and not subjected to a solution heat treatment after hot rolling.

[0024] [2] The hot-rolled steel material for cans according to [1], further comprising one or two of the following Group A and Group B in place of a portion of the Fe.

[0025] [Group A]

[0026] In terms of mass %, at least one of Sn: 0.050% or less, W: 1.00% or less, Co: 1.00% or less, Ca: 0.0050% or less, Mg: 0.0030% or less, and REM: 0.10% or less.

[0027] [Group B]

[0028] In terms of mass %, at least one of V: ​​0.30% or less, Nb: 0.060% or less, Ti: 0.030% or less, B: 0.0050% or less, Zr: 0.050% or less, Hf: 0.100% or less, and Ta: 0.100% or less.

[0029] [3] The hot-rolled steel material for cans according to [1] or [2], characterized in that the hydrogen content in the surface layer portion from the surface of the steel material to 1 / 5 of the plate thickness in the depth direction is set to H S , the hydrogen content in the center of the steel thickness is set as H C When H S / H C ≤0.85.

[0030] [4] The method for producing a hot-rolled steel material for cans according to any one of [1] to [3], characterized in that the water vapor partial pressure (p H2O ) and oxygen partial pressure (p O2 ) in an atmosphere satisfying the following formula (2) and heating a cast material having a thickness of T mm (T 2 / 140) minutes or more, and then hot-rolled to produce hot-rolled steel for cans.

[0031] LOG(p H2O / √(p O2 ))≤1.00(2)

[0032] Where LOG is the common logarithm with base 10, p H2O and p O2 The unit is (atm).

[0033] [5] The method for producing a hot-rolled steel material for a can according to any one of [1] to [3], characterized in that an intermediate rolled material having a thickness of T1 mm is produced by hot-rolling a cast material, and the intermediate rolled material is heated to a temperature of 100°C under a water vapor partial pressure (p H2O ) and oxygen partial pressure (p O2 ) is heated in an atmosphere satisfying the following formula (2) (T1 2 / 200) minutes or more, and then hot-rolled to produce hot-rolled steel for cans.

[0034] LOG(p H2O / √(p O2 ))≤1.00 (2)

[0035] Where LOG is the common logarithm with base 10, p H2O and p O2 The unit is (atm).

[0036] [6] The method for producing hot-rolled steel for cans according to [4], characterized in that the hot rolling is carried out at a final rolling temperature below 1000°C, and water cooling is carried out from 600°C or above after rolling without solution heat treatment.

[0037] [7] The method for producing hot-rolled steel for cans according to [5], characterized in that the hot rolling is carried out at a final rolling temperature below 1000°C, and water cooling is carried out from 600°C or above after rolling without solution heat treatment.

[0038] According to the present invention, when an end plate of a can is manufactured using austenitic stainless steel, that is, a hot-rolled steel material for a can having a tensile strength of 600 MPa or more without solution heat treatment, the occurrence of delayed fracture can be prevented. DETAILED DESCRIPTION

[0039] As the hot-rolled steel material for cans targeted by the present invention, thick plates are mainly used. As the plate thickness, steel materials with a thickness of 8 mm or more, further preferably 12 mm or more, and 20 mm or more are used.

[0040] The hot-rolled steel for cans of the present invention is a hot-rolled steel material of austenitic stainless steel having a tensile strength of 600 MPa or more. In order to achieve a tensile strength of 600 MPa or more, the steel material contains the component composition described below, and in the finishing rolling stage of hot rolling, processing strain is introduced by rolling, and controlled cooling is performed to increase the cooling rate of the steel material after rolling, and the solution heat treatment after rolling is omitted.

[0041] As described above, the following austenitic stainless steel hot-rolled steel material was used as the raw material for the end plate of the tank. As a result, it was found that delayed fracture occurred after plastic working as the end plate. The austenitic stainless steel hot-rolled steel material was a thick plate that had not been solution heat treated and had a tensile strength of more than 600 MPa.

[0042] Since cracks occur in the part subjected to plastic working, which causes delayed fracture, the transformed martensite phase generated by the work-induced martensite transformation caused by plastic working is assumed to be the starting point of cracks. In addition, the residual stress accompanying plastic working can be a driving force for crack generation.

[0043] As described above, in order to suppress the formation of the processing-induced martensite phase accompanying plastic deformation, it is effective to reduce the value of Md30 based on the component composition. In the present invention, as the formula of Md30, the following formula is used, which is obtained by adding the Cu term as a contribution equivalent to that of Ni based on the Angel's formula described in the above-mentioned non-patent document 1.

[0044] Md30(℃)=413-462(C+N)-9.2Si-8.1Mn-13.7Cr-9.5(Ni+Cu)-18.5Mo(1)

[0045] In the formula (1), the element symbol on the right side refers to the content (mass %) of the element in the steel.

[0046] It is known that in austenitic stainless steel, if thin plates are used as the object, in thin plates that have been bright annealed at the stage of steel strips, delayed fracture (spontaneous cracking) is likely to occur during deep drawing with a high degree of processing. Since bright annealing is performed in a hydrogen-containing atmosphere, hydrogen invades the steel during annealing and the hydrogen content in the steel increases, which is considered to be one of the factors causing spontaneous cracking. The steel material that the present invention is the object of is a thicker steel material that has not been bright annealed. On the other hand, it is assumed that in the manufacturing stage of the steel material that the present invention is the object, when the concentration of hydrogen contained in the molten steel is high, the hydrogen content of the final hot-rolled steel material increases. In particular, since no solution heat treatment is performed after hot rolling, the hydrogen in the steel material has less chance to be reduced by diffusion, which can also be a reason for the high hydrogen content in the steel material. It is estimated that the thicker the plate thickness of the steel material after hot rolling becomes, the lower the degree of hydrogen release caused by diffusion, and the higher the residual hydrogen content in the steel material becomes. Therefore, it is thought that spontaneous cracking during processing of end plates of steel materials for tanks can be reduced by reducing the hydrogen content in the steel materials.

[0047] When the steel for the tank is subjected to end plate processing, the hardness of the steel increases due to plastic processing. In the thickness direction of the steel, the degree of increase in hardness is large, especially near the surface. The tensile residual strain caused by plastic processing also tends to increase on the surface of the steel. Therefore, for spontaneous cracking generated in the end plate, the surface of the steel is also considered to be the starting point. Therefore, as mentioned above, when reducing the hydrogen content in the steel to prevent the occurrence of spontaneous cracking, special attention is paid to reducing the hydrogen content near the surface of the steel. As the surface part, the part from the surface of the steel to 1 / 5 of the plate thickness in the depth direction is taken as the object.

[0048] The steel (cast material before rolling, intermediate rolling raw material during rolling, and steel after rolling) is heated to a high temperature and heated under a hydrogen partial pressure (p H2 ) is maintained in an atmosphere with low carbon content, and the hydrogen content can be reduced by the diffusion of hydrogen in the steel. In the diffusion of hydrogen, the hydrogen concentration near the surface layer decreases in the initial stage of heating, and the hydrogen in the center of the steel also decreases in sequence. Here, if the occurrence of spontaneous cracking can be suppressed by reducing the hydrogen content in the surface layer of the steel (the portion from the surface of the steel material to 1 / 5 of the plate thickness in the depth direction), it becomes unnecessary to dehydrogenate the thickness center of the steel material, and thus the heat treatment time for reducing hydrogen in the steel can be shortened.

[0049] Based on the above idea, the casting material before rolling and the intermediate rolling material during rolling were subjected to the hydrogen partial pressure (p H2) is heated at high temperature for a long time in an atmosphere with low carbonization temperature. These materials are hot rolled and controlled cooled to produce steel without solution heat treatment. Then, the H (hydrogen) content from the surface of the steel material to the surface layer portion that is 1 / 5 of the plate thickness in the depth direction is analyzed.

[0050] The composition of the steel material is changed within the range of austenitic stainless steel to make various changes to the value of Md30 in the above formula (1), and the heat treatment conditions of the cast material before rolling and the intermediate rolling raw material during rolling are changed to variously change the hydrogen content in the surface layer of the steel material. The manufactured steel material is processed into an end plate of a tank, and the occurrence of spontaneous cracking is evaluated. The results show that if Md30 in formula (1) is below 35°C and the hydrogen content in the surface layer of the steel material is below 3.5 mass ppm, the occurrence of spontaneous cracking can be suppressed even if the end plate is processed, thereby completing the present invention.

[0051] Hereinafter, the present invention will be described in detail.

[0052] First, the chemical composition of the steel material of the present invention will be described. Hereinafter, % means mass %.

[0053] C: 0.08% or less

[0054] In order to ensure the corrosion resistance of stainless steel, the C content is limited to 0.08% or less.

[0055] The lower limit of C is not set, but is preferably set to 0.01% or more for the reason of ensuring strength.

[0056] Si: 0.05-1.0%

[0057] For deoxidation during steel smelting, Si is added in an amount of 0.05% or more, but if added in an amount exceeding 1.0%, toughness decreases, so the upper limit is made 1.0%.

[0058] Mn: 0.10~2.0%

[0059] In order to reduce the deterioration of hot workability caused by S, Mn is added in an amount of 0.10% or more. However, if an excessive amount of Mn is contained, deterioration of toughness, corrosion resistance, etc. occurs, so the upper limit is made 2.0%.

[0060] P: 0.045% or less

[0061] Since P is an impurity and deteriorates the hot workability and toughness of steel, the upper limit is made 0.045%, preferably 0.035% or less.

[0062] S: 0.030% or less

[0063] Since S is an impurity and deteriorates the hot workability, toughness and corrosion resistance of steel, the upper limit is made 0.030%, preferably 0.010% or less.

[0064] Cr: 18.0~20.0%

[0065] In order to ensure the basic corrosion resistance of steel, Cr is contained at 18.0% or more. On the other hand, if it exceeds 20.0%, the austenite stability decreases. Therefore, the Cr content is set to 18.0 to 20.0%.

[0066] Ni: 8.0~13.0%

[0067] In order to stabilize the austenite structure of the steel and improve the corrosion resistance and toughness to various acids, Ni is contained at 8.0% or more. On the other hand, Ni is an expensive alloy, and the upper limit is limited to 13.0% from the viewpoint of cost.

[0068] Mo: 1.0% or less

[0069] Mo is a very effective element for additionally improving the corrosion resistance of stainless steel, and can be contained as needed. Therefore, it is preferably contained at least 0.2%. On the other hand, since it is a very expensive element, the upper limit is limited to 1.0%. Mo may not be contained.

[0070] Cu: 1.0% or less

[0071] Cu is an element that additionally improves the corrosion resistance of stainless steel to acid and has the effect of improving toughness, so it can be contained as needed. Therefore, it is preferably contained at least 0.3%. On the other hand, if excessively added, εCu precipitates and causes embrittlement, so the upper limit is limited to 1.0%. Cu may not be contained.

[0072] N: 0.03~0.10%

[0073] N is contained at 0.03% or more for the purpose of stabilizing the austenite phase and strengthening the solid solution. On the other hand, if N is contained excessively, Cr nitrides precipitate and the corrosion resistance decreases, so the upper limit is made 0.10%.

[0074] Al: 0.10% or less

[0075] Al is an important element for deoxidation of steel. In order to reduce oxygen in steel, it can be contained together with Si as needed. Therefore, it is preferably contained at 0.01% or more. On the other hand, Al is an element with a relatively large affinity with N. If excessively added, AlN will be produced and the toughness of the steel will be impaired. The degree also depends on the N content, but if Al exceeds 0.10%, the toughness decreases significantly, so the upper limit of its content is set to 0.10%. Al may not be contained.

[0076] In the chemical composition of steel, the remainder is made up of Fe and impurities.

[0077] The steel material of the present invention is allowed to further contain trace elements such as B, Ti, Nb, Sn, V, W, Co, Ta, Ca, Mg, Zr, Hf, and REM as impurities in place of a portion of the above-mentioned Fe. The upper limits of the allowed contents are B: 0.0050% or less, Ti: 0.030% or less, Nb: 0.060% or less, Hf: 0.100% or less, Sn: 0.050% or less, V: 0.30% or less, W: 1.00% or less, Co: 1.00% or less, Ta: 0.100% or less, Ca: 0.0050% or less, Mg: 0.0030% or less, Zr: 0.050% or less, and REM: 0.10% or less. These optional elements are not essential, so the lower limit of the content is 0.

[0078] Sn: 0.050% or less

[0079] Sn is an element that additionally improves the corrosion resistance of stainless steel to acid, similar to Cu. This effect can be obtained even with a trace amount of addition, but in order to reliably obtain the effect, it is preferably contained at least 0.001%. On the other hand, Sn is an element that is harmful to hot workability, and if it is contained in excess of 0.050%, it may hinder hot workability. Therefore, the upper limit is set to 0.050%. The preferred content when added is 0.003 to 0.030%.

[0080] W: 1.00% or less

[0081] W is an element that improves the corrosion resistance of stainless steel, similarly to Mo. This effect can be obtained even with a trace amount of addition, but in order to reliably obtain the effect, it is preferably contained at least 0.01%. On the other hand, a large amount of addition leads to increased costs, so the content is set as 1.00% as the upper limit in the steel of the present invention. The preferred content when added is 0.1 to 0.5%.

[0082] Co: 1.00% or less

[0083] Co is an element effective for improving the toughness and corrosion resistance of steel. Even a trace amount of addition can achieve this effect, but in order to reliably achieve the effect, it is preferably added 0.01% or more. If it exceeds 1.00%, it will not be able to exert the effect consistent with the cost because it is an expensive element, so the upper limit is set to 1.00%. The preferred content when added is 0.1 to 0.5%.

[0084] Ca: 0.0050% or less, Mg: 0.0030% or less, REM: 0.10% or less

[0085] Ca, Mg, and REM are elements that improve the hot workability of steel and are added as needed. Here, REM refers to rare earth elements, and its content is set to the sum of the contents of rare earth elements. In addition, these elements are strong oxide-forming elements, and they form relatively large oxides in steel, which have the effect of hindering the toughness of steel. Even a trace amount of addition can achieve these effects, but in order to reliably obtain the effects, it is preferably set to Ca: 0.0003~0.0050%, Mg: 0.0001~0.0030%, REM: 0.005~0.10%, and more preferably Ca: 0.0010~0.004%, Mg: 0.0003~0.002%, REM: 0.010~0.06%.

[0086] V: 0.30% or less

[0087] V is an element that has affinity with N and C and has the function of forming nitrides and carbides. This nitride-forming effect is slightly smaller than that of other nitride-forming elements specified in the present invention, and is allowed to be contained up to 0.30%. However, if it is contained in an amount exceeding 0.30%, a large amount of nitrides and carbides of V may precipitate, which may hinder toughness, so the upper limit is set to 0.30%.

[0088] Nb: 0.060% or less

[0089] Nb is an element that has a stronger affinity with N and C than V and easily forms nitrides and carbides. If contained in excess of 0.060%, a large amount of Nb carbonitrides may precipitate and impair toughness, so the upper limit is made 0.060%.

[0090] Ti: 0.030% or less

[0091] Ti and N have a very strong affinity, and Ti nitrides are formed in the steel. Therefore, if contained, it must be set to a very small amount. If contained in excess of 0.030%, the toughness may be impaired by Ti nitrides, so the upper limit is set to 0.030%.

[0092] B: 0.0050% or less

[0093] B is an element having a very strong affinity with N. If contained in a large amount, nitrides of B may precipitate and thus impair toughness. Therefore, the upper limit of its content is made 0.0050%.

[0094] Zr: 0.050% or less, Hf: 0.100% or less, Ta: 0.100% or less

[0095] Zr and Hf are elements with strong affinity to N, and Ta is an element with strong affinity to N and C. If these elements are contained in large amounts, these carbonitrides may precipitate and impair toughness. Therefore, the upper limits of the contents of Zr, Hf, and Ta are set to 0.050%, 0.100%, and 0.100%, respectively.

[0096] As for the component composition, as described above, the Md30 of formula (1) is set to 35°C or less. This can suppress the processing-induced martensitic transformation during plastic processing such as end plate processing, and complement the hydrogen reduction in the surface layer of the steel material described later, and can suppress the occurrence of spontaneous cracking. Md30 is preferably 30°C or less. More preferably, it is 25°C or less.

[0097] In the steel material of the present invention, the H (hydrogen) content of the surface layer from the surface of the steel material to 1 / 5 of the plate thickness in the depth direction is set to 3.5 mass ppm or less. A portion from the surface of the steel material to 1 / 5 of the plate thickness in the depth direction is cut out as a sample. By adjusting the size of the sample in the width direction and the length direction of the steel material so that the mass of the sample becomes 0.5g or more, the accuracy of hydrogen analysis can be ensured. For the cut sample, the hydrogen content is analyzed using the inert gas-column separation-thermal conductivity method.

[0098] Next, the method for producing the hot-rolled steel material for cans of the present invention will be described.

[0099] First, a production method for setting the H (hydrogen) content in the surface layer portion from the surface of the steel material to 1 / 5 of the plate thickness in the depth direction to 3.5 mass ppm or less will be described.

[0100] For either the cast material before rolling or the intermediate rolling material during rolling, the hydrogen partial pressure (p H2 ) is a treatment in which hydrogen is diffused in the steel and released from the surface of the steel, thereby reducing the hydrogen concentration in the steel, especially the hydrogen concentration near the surface of the material.

[0101] For the hydrogen partial pressure in the atmosphere (p H2 ), it is necessary to set it to a value such that the hydrogen concentration in the steel in equilibrium with the hydrogen partial pressure becomes sufficiently low. In the present invention, if the hydrogen partial pressure in the atmosphere is set so that the hydrogen concentration in the steel in equilibrium becomes 2 mass ppm or less, dehydrogenation from the steel can be promoted. Since the hydrogen partial pressure that satisfies such a condition is very low, it is difficult to determine it directly by analyzing the atmosphere. On the other hand, according to the equilibrium relationship between hydrogen, oxygen, and water vapor in the atmosphere, the hydrogen partial pressure (p H2 ), water vapor partial pressure (p H2O ) and oxygen partial pressure (p O2 ) satisfy the following relationship.

[0102] p H2 ∝p H2O / √(p O2 )

[0103] Therefore, it is thought that if the water vapor partial pressure (p H2O ) and oxygen partial pressure (p O2 ), then the hydrogen partial pressure (p H2 ) level. In addition, various experiments were conducted and it was found that if the water vapor partial pressure (p H2O ) and oxygen partial pressure (p O2 ) If heat treatment is carried out in an atmosphere satisfying the following formula (2), hydrogen will be released from the surface of the steel during the heat treatment, which can reduce the hydrogen content in the steel.

[0104] LOG(p H2O / √(p O2 ))≤1.00 (2)

[0105] Where LOG is the common logarithm with base 10, p H2O and p O2 The unit of is (atm). LOG(p H2O / √(p O2 )) is preferably 0.90 or less, and more preferably 0.50 or less.

[0106] In the present invention, in order to manufacture a product in which the hydrogen concentration in the surface layer of the steel material after hot rolling is 3.5 mass ppm or less, the following manufacturing process can be adopted. The first method is: the casting material (thickness Tmm) is heated for a long time to release hydrogen from the surface of the casting material, and then hot rolling is performed to manufacture. The second method is: the casting material is subjected to the usual pre-hot rolling heating, and then the casting material is hot rolled to manufacture an intermediate rolling raw material with a thickness of T1mm, and the intermediate rolling raw material is heated for a long time to release hydrogen from the surface of the intermediate rolling raw material, and then further hot rolling is performed to manufacture. The following will be explained in sequence.

[0107] The first method will be described.

[0108] A casting material with a thickness of T = 140 mm was prepared. The hydrogen concentration in the casting material was analyzed and the results showed that the concentration was about 6 mass ppm near the surface and in the center of the plate thickness.

[0109] LOG(p H2O / √(p O2 ))=-0.178

[0110] In a heating furnace with an atmosphere of a heat treatment temperature of 950 to 1250°C, the time from when the surface temperature of the steel reaches 950°C to when it is extracted is set to Δt1, and a heat treatment of Δt1 = 129 minutes is performed. The surface temperature of the steel at the time of extraction, that is, the heat treatment temperature, is 1205°C. Afterwards, the steel is made into a plate thickness of 12 mm by hot rolling. The hot rolling method adopts the controlled cooling described later, and no solution heat treatment is performed. By the above method, the H (hydrogen) content from the surface of the steel to the surface layer that is 1 / 5 of the plate thickness in the depth direction is analyzed, and a result of 2.7 mass ppm can be obtained (sample No. 2 described later). The hydrogen concentration in the central part of the plate thickness of the steel is 3.4 mass ppm.

[0111] According to the basic characteristics of the unsteady diffusion equation, it can be understood that when the thickness T of the casting is changed, in order to make the hydrogen distribution diagram in the thickness direction of the casting the same at the same heat treatment temperature (i.e., the same hydrogen diffusion coefficient), the heat treatment time and T must be proportional. 2 As mentioned above, when T = 140 mm, the hydrogen concentration in the surface layer of the steel can be well maintained at 2.9 mass ppm when the heat treatment temperature is 1192 ° C and Δt1 = 120 minutes (sample No. 3 described later). Here, it is confirmed that in order to obtain the result of setting the hydrogen concentration in the surface layer of the steel to 3.5 mass ppm or less at different casting thicknesses T, when the heat treatment temperature is above 1000 ° C, Δt1 must be set to (T 2 / 200) minutes or more. The actual test was conducted on the casting material with T: 140~200mm, and the results confirmed that by setting the heat treatment temperature to above 1000℃ and the heat treatment time to (T 2 / 200) minutes or more, the hydrogen concentration in the surface layer of the steel material can be reduced to 3.5 mass ppm or less.

[0112] The second method will be described.

[0113] A casting material with a thickness of T = 200 mm was prepared in the manner of Sample No. 7 in Table 2 described later. The hydrogen concentration in the casting material was analyzed and the results showed that the concentration was about 5.4 mass ppm near the surface and in the center of the plate thickness. The material was subjected to the usual pre-hot rolling heating and hot rolling to produce an intermediate rolling material with a thickness of T1 = 120 mm. For the intermediate rolling material,

[0114] LOG(p H2O / √(p O2 ))=-0.117

[0115] In an atmosphere with a heat treatment temperature of 1182°C, a heat treatment of Δt1=80 minutes as defined above was performed. Afterwards, a steel material with a plate thickness of 20 mm was produced by hot rolling. The hot rolling method adopted the controlled cooling described later, and no solution heat treatment was performed. By the above method, the H (hydrogen) content of the surface layer from the surface of the steel material to 1 / 5 of the plate thickness in the depth direction was analyzed, and the result was 3.1 mass ppm. The hydrogen concentration in the central part of the plate thickness of the steel material was 5.2 mass ppm.

[0116] As in the first method, in the second method, it was confirmed that when various thicknesses were used as the thickness T1 mm of the intermediate rolling raw material, in order to obtain a result in which the hydrogen concentration in the surface layer of the steel material was set to 3.5 mass ppm or less, the heat treatment time had to be set to (T1 mm) when the heat treatment temperature was 1000° C. or higher. 2 / 300) minutes or more. The actual test was conducted on the casting material with T1: 90 to 130 mm. The results confirmed that by setting the heat treatment temperature to above 1000°C and the heat treatment time to (T1 2 / 300) minutes or more, the hydrogen concentration of the surface layer of the steel can be reduced to less than 3.5 mass ppm. As mentioned above, by thinning the intermediate rolling raw material thickness, the heat treatment time required for dehydrogenation can be shortened, but multiple rolling will greatly hinder productivity, so intermediate rolling is not performed more than 2 times. It should be noted that even if it is left for a long time at room temperature, there is no change in hydrogen concentration that has an impact on practical use.

[0117] As indicated by the above description, in the above-mentioned first and second methods, when the heat treatment temperature is set to a prescribed temperature of 1000°C or above in the heat treatment for reducing hydrogen from the steel by diffusion, the same or higher results as above can be achieved under the same conditions as above. When the heat treatment temperature changes, the diffusion coefficient of hydrogen in the steel changes, and therefore the heat treatment time required to reduce the hydrogen in the steel also changes. The required heat treatment time is proportional to the inverse of the diffusion coefficient. It is confirmed that in the austenitic stainless steel that is the subject of the present invention, the diffusion coefficient of hydrogen D (cm 2 / s) according to the following formula. Therefore, the degree of difference in diffusion coefficient can be calculated from the difference in heat treatment temperature, and the required heat treatment time at the changed heat treatment temperature can be calculated.

[0118] D = 7.4 × 10 -3 exp(-14400 / Rθ)

[0119] Wherein, θ is the heat treatment temperature (K), and R is the gas constant.

[0120] In addition, the upper limit of the heat treatment temperature is not set, but since the structure is coarsened during high-temperature heat treatment, the strength and toughness are reduced, so it is preferably set to 1250° C. or lower.

[0121] The conditions for hot rolling and controlled cooling after rolling are characterized in that finish rolling is performed at a final rolling temperature of 1000°C or less, and the steel is cooled by water cooling from 600°C or more after rolling without performing a solution heat treatment.

[0122] Thereby, it is possible to obtain a steel material that achieves both high strength due to the introduction of strain below the recrystallization temperature and corrosion resistance due to the suppression of Cr carbide precipitation.

[0123] The hot rolled steel of the present invention is not subjected to solution heat treatment after hot rolling. This can be confirmed by observing the structure of the hot rolled steel using EBSD (electron backscatter diffraction) to find that there is a structure region with a KAM value of 1 degree or more.

[0124] The hot rolled steel of the present invention, even when the cast material contains high concentration of hydrogen at the casting stage, is subjected to high temperature heat treatment in a predetermined atmosphere at the stage of the cast material or the intermediate rolling raw material, thereby reducing the hydrogen concentration in the surface layer by diffusion of hydrogen from the surface. Therefore, the hydrogen content in the surface layer from the surface of the steel material to 1 / 5 of the plate thickness in the depth direction is set as H S , the hydrogen content in the center of the steel thickness is set as H C When H S / H C ≤0.85.

[0125] Example

[0126] The following describes embodiments of the present invention.

[0127] Table 1 shows the chemical composition of the test material, the H content in the molten steel, Md30, and the slab thickness. It should be noted that the components other than those described in Table 1 are Fe and impurity elements. The elements whose content is indicated as "0" in Table 1 mean that they are not actively added. Regarding the H content in the molten steel, after the molten steel sample was water-cooled, it was analyzed using the inert gas-column separation-thermal conductivity method. These steels were melted by a real machine refining furnace, collected from slabs cast by a continuous casting device, and hot-rolled under the conditions shown in Tables 2 and 3. The hydrogen content and tensile properties in the steel were evaluated, and the results are shown. In Tables 2 and 3, Inventive Examples No. 1 to 4, 16, 17, Comparative Examples No. 28 and 29 were subjected to the heat treatment of the present invention at the stage of cast materials. Inventive Examples No. 5 to 15, 18 to 27, and Comparative Examples No. 30 to 34 were subjected to the heat treatment of the present invention at the stage of intermediate rolling raw materials (intermediate rolling raw material thickness shown in Tables 2 and 3). Regarding the heat treatment conditions, the time from when the surface temperature reaches 950°C to when the sample is extracted in an atmosphere where the heat treatment temperature is TA (°C) in Table 1 is set as Δt1, and Δt1 is shown in Tables 2 and 3. H2O 、p O2 LOG(p H2O / √(p O2 The values ​​of )) for the heating of the cast material and the heating of the intermediate rolling material are shown in Tables 2 and 3. The finishing temperature of hot rolling and the water cooling start temperature are shown in Tables 2 and 3.

[0128] For the hydrogen content of the product, the area from the surface of the steel material to 1 / 5 of the plate thickness in the depth direction is defined as the "surface part", and the area including the center of the plate thickness is defined as the "center part". The size of the sample in the width direction and the length direction of the steel material is adjusted so that the mass of the sample is 0.5 g or more, and the hydrogen analysis sample is collected. The hydrogen content of the cut sample is analyzed using the inert gas-column separation-thermal conductivity method.

[0129] As the evaluation conditions for corrosion resistance, A: segmented structure in JIS G0571 oxalic acid electrolytic etching was regarded as acceptable (A), and other conditions were regarded as unacceptable (B).

[0130] For steel plates, delayed fracture (spontaneous cracking) after plastic working is evaluated. As an evaluation of delayed fracture, steels with plate thicknesses of 20, 12, and 8 mm are subjected to end plate processing using cold pressing. For steels of each plate thickness, two circular dish-shaped end plates with inner diameters of 2500, 2500, and 1800 mm and heights of 660, 660, and 470 mm are formed respectively. As an evaluation of spontaneous cracking, the presence or absence of spontaneous cracking at the circumferential ends of the end plates after being stored at room temperature for one month after forming is observed. If even one spontaneous crack is visually confirmed in the circumferential end, it is judged as "spontaneous cracking". Steels with a plate thickness of 40 mm are set as excluded from the evaluation object because they exceed the size of the end plate processing object using cold pressing. In the "spontaneous cracking" column of Tables 2 and 3, no spontaneous cracking is set as qualified (A), and the rest is set as unqualified (B).

[0131]

[0132]

[0133]

[0134] As shown in Table 2, it is known that the hot-rolled steel of the present invention containing the component composition of the present invention and manufactured by the preferred manufacturing method of the present invention has a hydrogen concentration of the surface layer of less than 3.5 ppm, a tensile strength of more than 600 MPa, good corrosion resistance and spontaneous cracking resistance, and exhibits excellent properties as a material for low-temperature tanks.

[0135] On the other hand, in Table 3, for the steels of Samples No. 28 to 34 that do not conform to the present invention, the hydrogen concentration in the surface layer exceeds 3.5 ppm or the tensile strength is less than 600 MPa. For Samples No. 28 to 30, a lot of hydrogen remains in the steel due to insufficient heating time or high hydrogen partial pressure during heating during heating of cast materials or intermediate rolling raw materials. As a result, the delayed fracture evaluation result is poor, and spontaneous cracking occurs during storage after can production. Sample No. 31 is a sample that has been solution heat treated after hot rolling. Although the amount of hydrogen in the steel is reduced, the processing strain introduced during hot rolling is recovered, and the tensile strength is less than 600 MPa. In addition, since the finishing temperature of hot rolling is high in Sample No. 32, the processing strain introduced is insufficient, and the tensile strength is less than 600 MPa. Since the water cooling start temperature of cooling after hot rolling is low in Sample No. 33, carbides are precipitated, and dual judgment is made in JIS G0571 oxalic acid electrolytic etching, and the corrosion resistance is reduced. Sample No. 34 had a high Md30, which caused excessive work-induced martensitic transformation during can production, resulting in poor delayed fracture evaluation results. In fact, spontaneous cracking occurred within 48 hours after can production.

[0136] As can be seen from the above embodiments, it is clear that: through the present invention, a hot-rolled steel for tanks and a method for manufacturing the same can be obtained, which will not cause delayed fracture after plastic working when used as a raw material for the end plate of a tank, and the hot-rolled steel for tanks is an austenitic stainless steel hot-rolled steel with a tensile strength of more than 600 MPa.

Claims

1. A hot-rolled steel material for cans, having the following chemical composition: in terms of mass%, C: 0.08% or less, Si: 0.05-1.0%, Mn: 0.10-2.0%, P: 0.045% or less, S: 0.030% or less, Cr: 18.0-20.0%, Ni: 8.0-13.0%, Mo: 1.0% or less, Cu: 1.0% or less, N: 0.03-0.10%, Al: 0.10% or less, the remainder being Fe and impurities, The Md30 represented by the formula (1) is 35°C or less, The H (hydrogen) content in the surface layer from the surface of the steel material to 1 / 5 of the plate thickness in the depth direction is 3.5 mass ppm or less, The tensile strength has a value of 600 MPa or more, Md30(℃)=413-462(C+N)-9.2Si-8.1Mn-13.7Cr-9.5(Ni+Cu)-18.5Mo(1) In the formula (1), the element symbol on the right side refers to the content (mass %) of the element in the steel, and the "hot-rolled steel" refers to a steel in a hot-rolled state and not subjected to a solution heat treatment after hot rolling.

2. The hot-rolled steel material for cans according to claim 1, wherein: Further containing one or two of the following groups A and B to replace a part of the Fe, [Group A] In terms of mass%, at least one of Sn: 0.050% or less, W: 1.00% or less, Co: 1.00% or less, Ca: 0.0050% or less, Mg: 0.0030% or less, and REM: 0.10% or less, [Group B] In terms of mass %, at least one of V: ​​0.30% or less, Nb: 0.060% or less, Ti: 0.030% or less, B: 0.0050% or less, Zr: 0.050% or less, Hf: 0.100% or less, and Ta: 0.100% or less.

3. The hot-rolled steel material for cans according to claim 1 or claim 2, characterized in that: The hydrogen content in the surface layer from the surface of the steel material to 1 / 5 of the plate thickness in the depth direction is set as H S , the hydrogen content in the center of the steel thickness is set as H C When H S / H C ≤0.

85.

4. The method for producing a hot-rolled steel material for cans according to claim 1 or claim 2, characterized in that: By the water vapor partial pressure (p H2O ) and oxygen partial pressure (p O2 ) in an atmosphere satisfying the following formula (2) and heating a cast material having a thickness of T mm (T 2 / 200) minutes or more and then hot rolled to produce hot rolled steel for cans. LOG(p H2O / √(p O2 ))≤1.00(2) Where LOG is the common logarithm with base 10, p H2O and p O2 The unit is (atm).

5. The method for producing a hot-rolled steel material for cans according to claim 1 or claim 2, characterized in that: The cast material is hot-rolled to produce an intermediate rolled material having a thickness of T1 mm. The intermediate rolled material is heated to a temperature of 100°C under a water vapor partial pressure (p H2O ) and oxygen partial pressure (p O2 ) is heated in an atmosphere satisfying the following formula (2) (T1 2 / 300) minutes or more and then hot rolled to produce hot rolled steel for cans. LOG(p H2O / √(p O2 ))≤1.00(2) Where LOG is the common logarithm with base 10, p H2O and p O2 The unit is (atm).

6. The method for manufacturing a hot-rolled steel material for cans according to claim 4, characterized in that: The hot rolling is performed at a final rolling temperature below 1000° C., and water cooling is performed from above 600° C. after rolling without performing a solution heat treatment.

7. The method for manufacturing a hot-rolled steel material for cans according to claim 5, characterized in that: The hot rolling is performed at a final rolling temperature below 1000° C., and water cooling is performed from above 600° C. after rolling without performing a solution heat treatment.

Citation Information

Patent Citations

  • Austenitic stainless steel hot rolled steel having satisfactory corrosion resistance, proof stress and low temperature toughness and its production method

    JP2006241590A